Laparoscopic Evaluation of Female Factor in Bangladeshi Infertile Couple (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Background: Infertility prevails in good number in our society, causing social disharmony and distress. Laparoscopy is now a very effective tool for diagnosis and evaluation of female infertility.Method: This cross sectional study was conducted in Infertility Unit of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, from July, 2012 to June 2014. The aim of the study is to identify common pelvic pathologies of female factor infertility by laparoscopy so that early detection and treatment modalities can be instituted. Total 230 sub fertile patients attending OPD were selected for this study. Patients with DM, HTN, known case of hypothyroidism and male factor infertility was excluded from study. Detailed clinical history of every patient was recorded on a pre-set questionnaire and physical examination was performed. Laparoscopy was scheduled in proliferative phase of menstrual cycle.Results: Among the study subjects, 130 (56.5%) had primary infertility while 100 (43.5%) secondary infertility. On laparoscopy, 64.4% patient had normal sized uterus, 31 % had bulky uterus. Two patients had bicornuate uterus in secondary infertility cases. Uterus was restricted in mobility in 41% of patients due to endometriosis, pelvic inflammatory disease (PID) or previous pelvic surgery. Fibroid uterus was detected in 30(13%) and 10(4.3%) cases of primary and secondary infertility cases respectively. Bilateral tubal blockage was present in 16(6.9%) and 17 (7.4%) cases of primary and secondary infertility respectively. Forty (17.4%) cases of primary infertility were detected as polycystic ovaries (PCO) which was 30(13%) in cases of secondary infertility. Endometriosis was found in total 9(3.9%) patient in both the groups. Pelvic adhesion was found in 22(9.5%) and 21 (9.1%) cases of primary and secondary infertility respectively.Conclusion: Laparoscopy could diagnose a substantial number of portion pelvic pathology. In a developing country like Bangladesh, earlier and justified intervention with laparoscopy can save time and expense of infertility treatment by diagnosing pelvic factor responsible for infertility.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 29-35